Pengembangan Agroindustri Kopi Arabika yang Berkelanjutan (Studi Kasus pada Koperasi Produsen Tani Hutan Giri Senang, Kabupaten Bandung, Jawa Barat) - Sopian, Shaliha Taqiya; Trimo, Lucyana; Perdana, Tomy; Charina, Anne (Universitas Galuh, 2025)
Coffee is one of the leading plantation commodities cultivated in various countries, including Indonesia. Bandung Regency is a significant producer of arabica coffee, having the highest production, largest area, and greatest productivity of arabica coffee in West Java. The vast potential of coffee makes it the main commodity at the Koperasi Produsen Tani Hutan Giri Senang (KPTHGS). This research aims to identify internal and external factors that play a role in business sustainability and formulate alternative development strategies for the arabica coffee agroindustry at KPTHGS using the Triple Bottom Line (TBL) approach. The research employs a qualitative method, gathering data through participatory observation, interviews, scientific journals, and documentation. The analytical tools utilized include the IFE, EFE, SWOT, and QSPM matrices. The research results show that the IFE matrix score is 3.069824 and the EFE matrix score is 3.20652, positioning KPTHGS in cell I of the IE matrix, indicating a growth and build position. The study concludes that the prioritized strategies for execution are maintaining product quality, developing and innovating products, establishing partnership cooperation with farmers or collectors as raw material suppliers, and expanding marketing networks by forming partnerships with cafes or distributors.